2019
DOI: 10.3389/fpsyg.2019.00585
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ecological Approach Reveals Early Executive Function Impairments in Huntington’s Disease

Abstract: Introduction: Impairments in executive functions are common in neurogenetic disorders such as Huntington’s disease (HD) and are thought to significantly influence the patient’s functional status. Reliable tools with higher ecological validity that can assess and predict the impact of executive dysfunction in daily-life performance are needed. This study aimed to develop and validate a novel non-immersive virtual reality task (“EcoKitchen”) created with the purpose of capturing cognitive and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 93 publications
3
14
0
1
Order By: Relevance
“…Júlio et al conducted research to get a comprehensive picture of the real-life executive deficits shown by Huntington's disease (HD) patients using a novel VR task – “EcoKitchen” (Júlio et al, 2016 , 2019 ). It was designed and developed to evaluate planning, multi-tasking, set-shifting, cognitive flexibility, self-monitoring, sequencing, divided attention and scanning skills.…”
Section: Virtual Reality Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…Júlio et al conducted research to get a comprehensive picture of the real-life executive deficits shown by Huntington's disease (HD) patients using a novel VR task – “EcoKitchen” (Júlio et al, 2016 , 2019 ). It was designed and developed to evaluate planning, multi-tasking, set-shifting, cognitive flexibility, self-monitoring, sequencing, divided attention and scanning skills.…”
Section: Virtual Reality Toolmentioning
confidence: 99%
“…In a first preliminary study, the authors showed that this VR-based task appeared sensitive to early deficits in both premanifest HD and manifest HD than controls, with clinical groups that showed an overall slower cognitive and motor performance and a higher number of attention errors (Júlio et al, 2016 ). In the following study, the same three groups underwent complete evaluation with EcoKitchen and traditional neuropsychological batter (e.g., Phonemic Verbal Fluency test, Semantic Verbal Fluency test, Stroop test, Symbol Digit Modalities Test, Digit Span Test, TMT and WCST) (Júlio et al, 2019 ). Manifest HD group showed deficits in all assessment measures with a statistically significant correlation between the EcoKitchen, traditional neuropsychological battery and HD clinical features.…”
Section: Virtual Reality Toolmentioning
confidence: 99%
“…Finally, the fact that significant differences were absent at the level of conventional neuropsychological test results between Pre-HD and CTRL participants leads us to hypothesize that the neuropsychological test battery used, even if extensive, was not sufficiently sensitive to the subtle and earliest changes that occur in HD cognition—subtle changes synonymous of small effect sizes, might need larger samples of premanifest gene carriers for testing novel hypotheses. Also, having a set of more ecological neuropsychological tests would probably help to better distinguish between the Pre-HD and CTRL groups, as cognitive assessment methods that resemble daily-life tasks have proven to be more successful at differentiating premanifest HD individuals far from estimated disease onset and controls [95, 96].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the main benefits of virtual reality for the evaluation of IADLs include affordability, safety, efficiency, applicability to a wide range of conditions and ease of data capture and qualification [21,34].…”
Section: Types Of Tests According To the Paradigm And Technologymentioning
confidence: 99%
“…Indeed, difficulties performing IADLs have been closely associated with deficits in executive functions, which increase the need to develop effective compensatory strategies to meet the demands of IADLs [3,18]. Deficits in executive functions are a predictor of participation and functional outcomes of various pathologies [19]; they occur in over 66% of patients having had a mild stroke [20] and predict functional outcomes at three, six, nine and twelve months in stroke patients [21,22]. EF has been found to explain 37% of the variance of functional status in individuals with mild cognitive impairment, unlike other cognitive processes [23].…”
Section: Introductionmentioning
confidence: 99%